THE IMPORTANCE AND PERFORMANCE ANALYSIS OF STORE ATMOSPHERE AT CABANA CAFE - Suawa, Randy . (Universitas Sam Ratulangi, 2018)
Abstract: The purpose of this research is to analyze the importance and performance of store atmosphere that be priority to enhance by Cabana Cafe. The type of this research is descriptive quantitative method by using Importance-Performance Anlaysis (IPA) as the analytical tool. Type of data used is primary data by spreading the questionnaires to the guests to gain information based on their perceptions and expectations where the sample size taken as much as 100 respondents. The result are measure in 14 service attributes which are (1) Friendly staff, Availability of menu, Customer access road, are plotted in Qudarant I where high importance level but the performance is perceived low, (2) Music, Information from the staff, Cleanliness are plotted in Quadrant II where the level of importance and performance is high, (3) Secure Parking, The smell room, Placement of the sign can be seen are plotted in Quadrant III where the level of importance and performance is low, (4) Entrance easily accessible to customer, Arrangment of the room, Lightning that attract customer, Air temperature, Layout of the table and chair are plotted in Quadrant IV where low importance level but have high performance level more than respondents expectations. In improving the store atmosphere to meet customersâ€™ expectations, Cabana CafÃ© has to evaluate the service attributes in Quadrant I.Keywords: importance-performance analysis